2023
DOI: 10.1088/1741-4326/acf946
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasma–atom and molecule interactions on power & particle balance during detachment on the MAST Upgrade Super-X divertor

K. Verhaegh,
B. Lipschultz,
J.R. Harrison
et al.

Abstract: This paper shows first quantitative analysis of the detachment processes in the MAST Upgrade Super-X divertor (SXD). We identify an unprecedented impact of plasma-molecular interactions involving molecular ions (likely $D_2^+$), resulting in strong ion sinks (Molecular Activated Recombination - MAR), leading to a reduction of ion target flux. The MAR ion sinks exceed the divertor ion sources before electron-ion recombination (EIR) starts to occur, suggesting that significant ionisation occurs outside of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
(184 reference statements)
4
7
0
Order By: Relevance
“…where R OSP and R OMP are the major radii of the outer strike point and the separatrix at the outer mid-plane respectively. These predictions are in qualitative agreement with previous Ohmic heated L-mode experiments on MAST-U [36,40], observing that the Super-X configurations facilitates access to the detached divertor regime.…”
Section: Impact On Outer Divertor Conditionssupporting
confidence: 90%
See 3 more Smart Citations
“…where R OSP and R OMP are the major radii of the outer strike point and the separatrix at the outer mid-plane respectively. These predictions are in qualitative agreement with previous Ohmic heated L-mode experiments on MAST-U [36,40], observing that the Super-X configurations facilitates access to the detached divertor regime.…”
Section: Impact On Outer Divertor Conditionssupporting
confidence: 90%
“…This roll-over behaviour in the outer divertor D α emission is not commonly observed, because and is thought to be due to low electron temperature and density conditions that prevail when the Super-X divertor configuration is detached in MAST-U, where plasmamolecule interactions produce a significant proportion of the Dα emission. At separatrix densities significantly exceeding the detachment threshold in the Super-X configuration, the electron temperature at the divertor target drops below 1 eV, reducing the source of molecular ions and their associated D α emission [36,40], causing the total emission from the divertor to fall with increasing separatrix density.…”
Section: The Mast Upgrade Scenario Integration Challengementioning
confidence: 99%
See 2 more Smart Citations
“…Detailed analysis of the physics mechanisms during detachment in the Super-X divertor have shown that plasmamolecular chemistry, including MAR and MAD, plays an unprecedentedly strong role in the tightly baffled divertor chambers when the ionisation source is significantly detached from the target. This results in a build-up of MAR downstream of the ionisation region towards the target [12,22].…”
Section: Mast Upgrade and The Super-x Divertormentioning
confidence: 99%